Dietary fish oil and the severity of symptoms in patients with systemic lupus erythematosus. Issue 7 (July 1991) - Walton, A J; Snaith, M L; Locniskar, M; Cumberland, A G; Morrow, W J; Isenberg, D A
Abstract : A prospective, double blind, cross over study assessing the effects of a low fat, high marine oil diet in 27 patients with active systemic lupus erythematosus has been performed. The patients were given 20 g daily of MaxEPA (eicosapentaenoic acid) or 20 g of olive oil (placebo) in matching capsules added to a standardised isoenergetic low fat diet. When individual outcome measures of the 17 patients who completed the full 34 week study were considered 14 who were receiving MaxEPA achieved useful or ideal status, whereas 13 receiving placebo were rated as worse or no change. The difference between the two types of capsule was statistically significant. No major side effects were noted, and it is suggested that dietary modification with additional marine oil may be a useful way of modifying disease activity in systemic lupus erythematosus.